Srinagar hernia: a rare case report - Patil, Aishwarya D.; Satpute, Anuprit; Sathe , Prashant (International Surgery Journal, 2025)
Testis and cord as content of sac in an indirect hernia is very rare. A 32-year-old male with scrotal swelling was diagnosed as a case of indirect inguinal hernia. Exploration documented indirect inguinal hernia of complete type with the spermatic cord and testicle as a content of sac. This is the unique case report with new type of indirect hernia reported with cord as the content of sac named as "Srinagar hernia". Indirect inguinal hernia with testis and spermatic cord as a content is very rare entity.